Datasets on the variations of minerals in biofortified cassava (Manihot esculenta Crantz) as a function of storage root portion, maturity and environment - Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Dixon, A. (F1000 Research Ltd, 2022)
Background: The accurate measurements of the mineral content of cassava roots are vital from a nutritional perspective. The research datasets were from the study assessing the influence of storage root portion, maturity, and environment on the variations of minerals in biofortified cassava roots. Methods: Twenty-five biofortified clones with three varieties as checks were harvested 12 months after planting from five different environments. Also, a different thirty-nine (39) biofortified cassava clones from the unlimited yield trials (UYTs) that included five (5) white-fleshed varieties (as control) were harvested at the age of 9 and 12 months after planting. In addition, two different methods of sample preparations were employed, using a cork borer and without a cork borer. The samples’ elemental (minerals) analysis was determined using a standard laboratory method. Results and conclusion: The breeders could use the data in their biofortification cassava programs to know the distribution of minerals in the roots and identify the best promising pipelines. Also, the data could be used by food scientists and nutritionists to understand the parts of the roots with optimum minerals to design their processing protocols and to know those genotypes specific to different environments that could be used for various nutrition intervention programs.